Shear failure mechanisms of SCS sandwich beams considering bond-slip between steel plates and concrete. (15th February 2019) - Lin, Youzhu; Yan, Jiachuan; Wang, Yonghui; Fan, Feng; Zou, Chaoying
Highlights: Shear failure mechanisms of SCS sandwich beams are explored. Structural behaviours of SCS sandwich beams are simulated by finite element models. Parametric studies on failure mechanisms of SCS sandwich beams are investigated. Theoretical analysis of SCS sandwich beams is carried out considering bond-slip. Abstract: The steel-concrete-steel (SCS) sandwich structure has been proposed for containment buildings in third-generation nuclear power plants. In this paper, 27 static tests on SCS sandwich beams (by the authors and others) are adopted serially to summarize the failure modes and explore the failure mechanisms of SCS sandwich beams with different bond-slip conditions between the steel plate and concrete. Further, a three-dimensional finite element (FE) model is developed to simulate the ultimate strength of SCS sandwich beams under different failure modes. The accuracy of the developed FE model in predicting ultimate strength, cracking behaviours and bond-slip behaviours is verified by static tests. Based on the validated FE model, 65 numerical cases are calculated to investigate the effects of analytical parameters on the failure mechanism and ultimate strength of SCS sandwich beams under different bond-slip conditions. The analytical parameters include the steel plate ratio, shear span to depth ratio, spacing of shear studs and shear reinforcement ratio. In addition, theoretical models are proposed to predict the ultimate strength of SCS sandwich beams under different bond-slip conditions. The accuracy of the theoretical model is verified by comparison with current design codes for SCS sandwich beams.